Self-reports of musculoskeletal symptoms as predictors of work-related accidents: A hospital-based case-control study - Bernardes, Joao Marcos [UNESP] (2019)
We present a hospital-based case-control study, which aimed to address the question: are self-reports of musculoskeletal symptoms associated with the occurrence of work-related accidents? The study was conducted among workers aged 17-59 years and residing in Botucatu, Brazil. Cases were workers who had had work-related accidents that required hospitalization, while controls included non-work-related accidents. Altogether, 80 cases and 125 controls were included. Self-reports of musculoskeletal symptoms were assessed by the Nordic Musculoskeletal Questionnaire. Associations between self-reports of musculoskeletal symptoms and work-related accidents were analyzed with logistic regression models. Our results show that self-reports of musculoskeletal symptoms in the upper limbs and in the vertebral column are associated with the occurrence of work-related accidents. Thus, this case-control study suggests (1) that musculoskeletal symptoms in the upper limbs and in the vertebral column are associated with increased odds of work-related accidents; and (2) that the Nordic Musculoskeletal Questionnaire may be used as a complementary screening tool for identifying workers at risk for work-related accidents.